Applying Read, Cover, Remember, and Retell (RCRR) Strategy to Increase Students’ Reading Comprehension of Recount Text - Nihayati Putri Suseno; ainol ainol; Achmad Kholili (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
In 2013 curriculum, reading competence section, students in high school are anticipated to be able comprehend concise functional texts in everyday situations, such as narrative, analytical exposition, recount, and descriptive texts. Meanwhile, a quasi-experimental design was used a test was given. Therefore, as to know students’ reading comprehension with pre-tests and post-tests. In current study, the writer therefore analyzes the data using Independent Sample T-test to find out if there is a significant in the mean, which compared the two distinct groups. This study's population 52 students were divided into two classes for the sample. using the purposive sampling method; X D the RCRR strategy was not applied to the controlled class, while X C was the experimental class. The study's findings demonstrated that students' reading comprehension of recount texts varied significantly between those who used the RCRR strategy and those who did not. It demonstrated that the RCRR method significantly improved the reading comprehension of recount texts for tenth-grade students at SMA Zainul Hasan 1 Genggong.